A comparative study of efficacy of ropivacaine (0.75%) with adjuvants – dexmedetomidine and fentanyl in supraclavicular brachial plexus block - Zaebha Shah Alam; Pradhan Monnaiah K; Sandeep S Kadam; Hema Viswanath K; Pedapolu Kishore Babu; Usha Rani S (Asian Journal of Medical Sciences, 2023)
Background: Brachial plexus block is preferred to general anesthesia (GA) as it reduces many complications of GA, provides good intra and postoperative analgesia, adequate muscle relaxation. Addition of adjuvants along with LA is used to prolong block with improved quality of anesthesia and decrease dose of LA. This study was done to see the efficacy of Ropivacaine with dexmedetomidine and fentanyl in terms of duration of action and pain relief. Aims and Objectives: Dexmedetomidine and Fentanyl along with Ropivacaine in patients undergoing upper limb surgeries, the onset and duration of sensory and motor blockade as well as post op analgesia is compared. Materials and Methods: Prospective Randomized Comparative study with three groups randomly divided received total volume of 30 mL of drug in peripheral nerve stimulator guided supraclavicular blocks in patients undergoing upper limb surgeries. Group Dexmedetomidine received 28 cc of 0.75% Ropivacaine and Dexmedetomidine (1 mcg/kg), Group Fentanyl patients received 28 cc of 0.75% Ropivacaine and fentanyl (1 mcg/kg), whereas, group plain Ropivacaine patients received 28 cc of 0.75% Ropivacaine and 2 mL of normal saline. Haemodynamics, sensory and motor block (MB) were evaluated by VAS and modified Bromage scale. Results: The onset of sensory block and MB in the dexmedetomidine group, fentanyl group, and ropivacaine groups was 3.57±0.50 min and 4.47±0.51 min, 5.50±0.51 min and 7.53±0.51 min, and 8.07±0.79 min and 10.07±0.79 min respectively which were statistically significant. The duration of MB in the dexmedetomidine group, fentanyl group, and ropivacaine group were 6.57±0.50 h, 4.47±0.51 h, and 2.50±0.51 h respectively which was statistically significant (P=0.0000). The duration at which first postoperative analgesia was required in the dexmedetomidine group, fentanyl group, and ropivacaine group were 8.57±0.50 h, 6.57±0.50 h, and 5.30±0.47 h respectively. Conclusion: Dexmedetomidine is better as an adjuvant to Ropivacaine for brachial plexus block in terms of onset and duration.